The impact of internal communication on guest satisfication in hospitality establishments in Cape Town - Bamporiki, Abdallah Seif (Cape Peninsula University of Technology, 2010)
Within the hospitality industry, where revenues are driven by guest satisfaction, service is a key to success. Internal communication plays a role that should be examined on how its performance affects guest satisfaction within hospitality. The purpose of this study is to determine if internal communication plays a role in guest satisfaction within hospitality establishments in Cape Town. The study found that sources (such as newsletters, magazines, books, journals and peers) emphasised importance of internal communication in hospitality organizations. This internal communication serves as a nerve centre of an organization. If one does not have a functioning internal communication system, one may lose guests. In addition, advanced internal communication solution forms a backbone of a wide range of guest services, and increases the guests’ motivation to stay. Cape Town, where hospitality and tourism is increasingly competitive and diverse, human resource management becomes more problematic. There should be channels of internal communication, which transmit messages across the organization’s structure. The guest’s review demonstrated that growth of hospitality organisation will be determined by its ability to deliver superior guest value and importance of understanding guest needs and expectation. The reason for growing emphasis on guest satisfaction is that satisfied guests lead to a stronger competitive positioning, resulting ultimately in loyal guests, increased market profitability. Management teams in Cape Town and hotel industry sectors are under increasing pressure to demonstrate that their services are guest-focused and that continuous performance improvement is being delivered. Internal communication research generates principles and strategies, which improve managerial performance, as internal communication acumen is essential to render success in a wide range of activities. Language proficiency, as well as what a manager says, and what a manager does, contributes to individual effectiveness. Furthermore, words and actions should be consistent and aligned so that they have maximum impact. Selected research findings regarding verbal internal communication and non-verbal internal communication as well as electronically are presented to demonstrate how wise internal communication choices can further managerial goals. In addition to using words effectively, managers in all functional areas can also increase their effect and improve their performance by applying results of research that are focused on internal communication. A self-administered questionnaire was compiled to collect data, and the study was based on 10 selected hotels within Cape Town and a great value is given to Cape Town business centre where most of tourism businesses held. Information was supplied by senior and junior managers from 4-5 star hotels and the final report combined results from the question about the role that internal communication plays in guest satisfaction within hospitality establishments in Cape Town by using an SPSS Program, while recommendations are also based on these findings. At this period of twenty one century, the technology is challenging organisational internal communication, it take major part in marketing and marketing research. The management are busy straggling with internal communication which they will never know exactly how much they perform without guest concert. They run to the Internet to research what the guests comment about their satisfaction of service they received. The guest reviews about hotel service industry emphasized the quality of service received within the hotel organization even if most of the hotels in Cape Town were too expensive as guest review recommended.
Thesis (MTech (Tourism and Hospitality Management))--Cape Peninsula University of Technology, 2010
Keywords: Hotels -- Customer services; Consumer satisfaction; Hotels -- Marketing